Antimicrobial stewardship programs and antibiotic use in Africa: A systematic review and meta-analysis protocol - Ammas Siraj Mohammed; Dawit Abrham (PLoS ONE, 2025)
Background Antimicrobial resistance (AMR) is a significant public health crisis, particularly in Africa where infectious disease burdens are high. While antimicrobial stewardship programs (ASPs) are a key intervention, a comprehensive synthesis of their impact on antibiotic use in this context is lacking. Objective This systematic review and meta-analysis aims to synthesize current evidence regarding the association between ASPs and antibiotic use in Africa. Methods MEDLINE (PubMed), Embase, CINAHL, Web of Science, and regional databases including african journals online and WHO global index medicus will be searched systematically. Original studies of the association of ASPs with antimicrobial consumption across healthcare settings will be included while Animal and environmental studies will be excluded. Two independent reviewers will screen articles, extract data, and assess quality using the Effective Public Health Practice Project (EPHPP) quality assessment tool. The main outcome measures will be proportion of patients receiving anantibiotic prescription and defined daily doses per 100 patient days. The pooled association of targeted ASPs with antimicrobial consumption will be be measured using multilevel random-effects models. Expected outcomes This systematic review and meta-analysis is expected to provide valuable, pooled evidence on the effectiveness of ASPs in reducing antimicrobial consumption in Africa. The findings will inform and call for evidence based interventions by governments and Non-Governmental Organizations (NGOs) to combat AMR in resource limited settings. Systematic review registration PROSPERO CRD420251003018.